2014
DOI: 10.3390/resources3010031
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Hedonic Studies to Assess the Property Value Effects of Low Impact Development

Abstract: Stormwater runoff from urban areas is a significant source of water pollution in the United States. Many states are promoting low impact development (LID) practices, which provide a variety of direct and ancillary ecosystem services. We describe a meta-analysis designed to evaluate the property value benefits of LID practices that reduce impervious surfaces and increase vegetated areas in developments, and present an example application to a hypothetical land use scenario. From the many hedonic property valuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…The integration of constructed wetland with urban living as a part of aesthetic co-design of water functioning services and urban landscape will not only provide a financially viable option (because the water purification is done by natural capital instead of market capital), but also offers numerous ecological services as mentioned above and additional urban design function such as more public spaces to promote social interactions, physical health and fitness, diminished crime and increased wellness, resulting in improving the quality of life within the livable, regenerative community (rather than the conventional mentality NIMBY-Not In My Back Yard) [99]. For example, hiking trails, and nature parks around the wetlands can offer public recreational space and increase aesthetic and property values [100].…”
Section: Fit For Purpose and Greywater/rainwater Reusementioning
confidence: 99%
“…The integration of constructed wetland with urban living as a part of aesthetic co-design of water functioning services and urban landscape will not only provide a financially viable option (because the water purification is done by natural capital instead of market capital), but also offers numerous ecological services as mentioned above and additional urban design function such as more public spaces to promote social interactions, physical health and fitness, diminished crime and increased wellness, resulting in improving the quality of life within the livable, regenerative community (rather than the conventional mentality NIMBY-Not In My Back Yard) [99]. For example, hiking trails, and nature parks around the wetlands can offer public recreational space and increase aesthetic and property values [100].…”
Section: Fit For Purpose and Greywater/rainwater Reusementioning
confidence: 99%
“…Paper [12] presents results of studies in the field of development of low-impact degree (LID) technologies that satisfy human needs. It was shown that the LID technologies enable solution of many human problems including environmental and similar ones.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…For more discussion on the various potential measures of the dependent variable in meta-analysis, see Borenstein et al (2009, chapter 4). Other recent papers that follow a similar standardization procedure in a meta-regression context are Rose and Dormady (2011) and Mazzotta et al (2014). In studies where impacts of particular type of disaster (e.g.…”
Section: Appendix Standard Of Dependent Variablesmentioning
confidence: 99%